2016
DOI: 10.1088/2040-8978/18/5/055706
|View full text |Cite
|
Sign up to set email alerts
|

Broadband optically controlled switching effect in a microfluid-filled photonic bandgap fiber

Abstract: Broadband optically controlled switching in a microfluid-filled photonic bandgap fiber (MF-PBGF) was observed and investigated. The MF-PBGF was formed by infusing a temperature-sensitive high-index fluid into all of the cladding holes of a microstructured optical fiber (MOF). The fiber was then side pumped with a 532 nm continuous wave laser. An extinction ratio of greater than 20 dB at most of the bandgap wavelengths (more than 200 nm) was obtained with a switching power of ∼147 mW. Theoretical and experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Moreover, for most of conventional photonic crystal photoswitches, "on-off" transition is usually realized through the shi of photonic bandgap or the migration of defect mode. [57][58][59] However, optical switching effect and/or contrast were usually limited by the slope of photonic bandgap edges due to small shi of reective peaks (Dl). By contrast, the present photonic crystal membrane exhibited a large Dl (it equals to l max of the photonic crystal) as no reective peaks existed in the deformed state, which provides a unique alternative in developing photonic crystal photoswitches with higher contrast and optical switching effect.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, for most of conventional photonic crystal photoswitches, "on-off" transition is usually realized through the shi of photonic bandgap or the migration of defect mode. [57][58][59] However, optical switching effect and/or contrast were usually limited by the slope of photonic bandgap edges due to small shi of reective peaks (Dl). By contrast, the present photonic crystal membrane exhibited a large Dl (it equals to l max of the photonic crystal) as no reective peaks existed in the deformed state, which provides a unique alternative in developing photonic crystal photoswitches with higher contrast and optical switching effect.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional controlling technologies are mainly based on electricity, mechanics or magnetism [1][2][3], which are technically mature and stable but sensitive to electromagnetic interference and lace of compactness. As a neotype technology, the all-optical controlling technology has been widely studied due to its small volume, immunity to electromagnetic interference and compatibility with optical networks [4][5][6][7][8][9][10][11][12][13]. At 2016, Schnack et al realized all-optical control through intermodal phase difference, which has a potential application to all-optical switches [9], and an all-optical switch has been demonstrated [10].…”
Section: Introductionmentioning
confidence: 99%
“…As a neotype technology, the all-optical controlling technology has been widely studied due to its small volume, immunity to electromagnetic interference and compatibility with optical networks [4][5][6][7][8][9][10][11][12][13]. At 2016, Schnack et al realized all-optical control through intermodal phase difference, which has a potential application to all-optical switches [9], and an all-optical switch has been demonstrated [10]. Based on the side pumped light controlling technology, Yu et al proposed and demonstrated a single longitudinal mode microring laser [11].…”
Section: Introductionmentioning
confidence: 99%
“…MF presents unique magnetooptical properties, including a tunable refractive index [3,4], dichroism and birefringence effects [5,6], Faraday rotation [7] and a thermal lens [8]. The application of MF has been extended to the optical and sensing fields, such as optical filter [9], optical switches [10] and optical modulators [11,12]. MF-based fiber-optic magnetic field sensors have the advantages of compactness and high sensitivity, and the magn etic field sensors based on different structures have been greatly developed and improved in recent years.…”
Section: Introductionmentioning
confidence: 99%